The implementation of Policy of Urban Village Fund From The Result Oriented government Perspective: (A Case Study in Manggala District, Makassar city) - Amin, Nur Ihsan; Saleh, Akhir (Institut Pemerintahan Dalam Negeri Kampus Sulawesi Selatan, 2024)
subdistrict funds have been disbursed since 2019, a number of subdistricts have used them well, but others still find problems in using the planned budget use due to various existing obstacles. This research aims to explore the extent of obstacles in utilizing sub-district funds which can provide benefits to the community in Manggala sub-district. the research was conducted using a qualitative descriptive approach using data collection techniques through interviews, observation and documentation. interviews were conducted with informants consisting of village heads, sub-district heads and other community figures such as community groups in the sub-district, rW, rt as well as community leaders who have an interest in the development of sub-district infrastructure and concepts of community empowerment in the sub-district. data analysis was carried out using the theory of Merilee S, Grindle (1980) which is influenced by two large variables, namely the Policy content variable and the Policy environment variable which is equipped with several sub-variables, the results of which show that Village fund management, although some can already be implemented, some other parts still encounter obstacles both in administrative and managerial aspects. in particular, it has not been implemented optimally, especially partnerships with local community groups as mandated by applicable laws and regulations.